Employee Workload Measurement Analysis Using the Full Time Equivalent Method in the Operational & Maintenance Division of PT. XYZ - Utomo, Nandy Lara Bestari; Hidayati, Roziana Ainul (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to measure employee workload in the Operational & Maintenance Division of PT XYZ using the Full Time Equivalent (FTE) method. This method is used to evaluate the optimal number of workers based on available working hours and actual activity time. The analysis results show that the workload of heavy equipment operators such as excavators, trailers, and bulldozers fall into the optimal category, while for cranes there is a shortage of workforce.